FACTORS CONTRIBUTING TO SHORTAGE OF DIABETES MEDICINES IN KAKINDO HEALTH CENTRE IV, KAKUMIRO DISTRICT - Namukisa, Felicity; Niwagira , Mulodokayi (Student's Journal of Health Research Africa, 2023)
FACTORS CONTRIBUTING TO SHORTAGE OF DIABETES MEDICINES IN KAKINDO HEALTH CENTRE IV, KAKUMIRO DISTRICT